Imaging findings of familial adenomatous polyposis-associated aggressive mesenteric fibromatosis: A case report - Stošić, Srdjan; Sotirović-Seničar, Slavica (Vojnosanitetski pregled, 2022)
Introduction. Aggressive fibromatosis, also known as desmoid type fibromatosis (DF) is a locally aggressive fibroblastic neoplasm that can arise anywhere in the body with no potential for metastasis and a high recurrence rate after surgical resection. Mesenteric fibromatosis are locally aggressive DF of the mesentery with a high propensity for bowel involvement. The real etiology of these tumors remains unknown, occurring sporadically or in association with familial adenomatous polyposis (FAP), as Gardnerʼs syndrome. Case report. A 34-year-old female patient presented with a palpable solid tumefactive mass in the left hemiabdomen. Contrast enhanced computed tomography (CT) and magnetic resonance imaging (MRI) revealed multiple massive solid tumefactions in the mesentery and in between the small bowel loops. Colonoscopy confirmed the presence of multiple sessile polyps characteristic of FAP. Tissue samples of the mesenteric mass were acquired via ultrasound guided biopsy with histopathologic confirmation of desmoid fibromatosis with imunohistochemical analysis. The risk of surgery was deemed too high at the time due to the size of the mass and proximity to mesenteric vascular structures, therefore the patient was planned for chemotherapy with a potential for further surgical reevaluation. Conclusion. Mesenteric fibromatosis is a rare neoplasm that presents with a wide range of histologic and imaging features. CT and MRI play a crucial role in evaluation and planning an optimal treatment model for patients with mesenteric fibromatosis.